HUBUNGAN KECERDASAN EMOSIONAL DENGAN KECERDASAN INTELEKTUAL PADA MAHASISWA PENJASKESREK - Yulinar, Yulinar; Rozal, M. Rizky; Kurniawan, Erizal; Syahrianursaifi, Syahrianursaifi; Husaini, Husaini (Jurnal Dedikasi Pendidikan, 2025)
The aim of the research is to determine the relationship between emotional intelligence and intellectual intelligence in Physical Education students at the Faculty of Teacher Training and Education, Abulyatama University. The research hypothesis is that there is a relationship between emotional intelligence and intellectual intelligence in Physical Education students at the Faculty of Teacher Training and Education, Abulyatama University. Correlation research method. The population is all Penjaskesrek FKIP Abulyatama University students, while the sample taken was 38 students. Data collection techniques through questionnaires distributed via Google Form. The data analysis technique uses a correlation formula. The results of the research showed that the average value and standard deviation of emotional intelligence were 83 and 2.30 and intellectual intelligence were 3.36 and 0.22. The correlation calculation result (r) is 0.73 and the t test calculation result is 6.44. To prove the results, the t-count was 6.44 and the t-table at the 95% significance level was 1.68 (t-count = 6.44 > t-table = 1.68), so the proposed research hypothesis was accepted as correct. This means that there is a relationship between emotional intelligence and intellectual intelligence in Physical Education and Physical Education students Faculty of Teacher Training and Education Abulyatama University